L'EBE DI CANOVA: MODELLO DIGITALE E SVILUPPI APPLICATIVI 2 PARTE - DE CRESCENZIO, FRANCESCA; FANTINI, MASSIMILIANO; PERSIANI, FRANCO; VIRGILLII, VALENTINA; SANTOPUOLI, NICOLA; SECCIA, LEONARDO (Archeomatica, 2012)
Canova's Ebe: digital model and application developments - 1stpart - In this paper the main aspects of a complex research project,performed by the CAILab and V-lab laboratories of the Second EngineeringFaculty of the Bologna University, are described. Thisproject is being developed exploiting some different laser scanningtechnologies, with the goal to obtain a 3D survey of the sculpturecalled Ebe of Antonio Canova that is conserved in Forlà¬.